O currículo de arte na educação de jovens e adultos: reflexão acerca de uma proposta curricular para o segundo segmento do ensino fundamental na rede municipal de educação de São Luís MA. - MACHADO, Rosifrance Candeira (2012)
This study is an analysis of the Art Curriculum Proposal for the II Segment of Youth and Adult Education (EJA), drawn by art teachers of the municipal network of São Luís/MA, linked to the Supervision of Youth and Adult Education Area (SAEJA). The study reflects about the text of the Proposed Curriculum, not yet published. And makes some relevant considerations to its disclosure, as well as its implementation in schools. Also analyze the teaching of Art practiced in schools of the municipal network, seeking information on documentary analyses, interviews and questionnaire application made on schools that offer the EJA. In the search were investigated four schools, about twenty students and four teachers of discipline, in addition to servers attached to SAEJA. The study is part of the research line LP2 Culture, Education and Society Program of Postgraduate Culture and Society Federal University of Maranhão (UFMA) Interdisciplinary Masters.